Comparative study of patient’s satisfaction with quality of maternal and child healthcare services in primary healthcare centres in urban and rural communities in Ekiti State, Nigeria - Adeniyi, Makinde A.; Adewoye, Kayode R.; Durowade, Kabir A.; Isa, Abdulfattah; Adebisi, Olusola O.; Azees, Ayotunde S. (International Journal Of Community Medicine And Public Health, 2026)
Background: Patients’ satisfaction is related to the extent to which general health care needs and condition specific needs are met. Evaluating the extent patients are satisfied is clinically relevant as satisfied patients are more likely to comply with medication and thus have a more positive health outcome. In sub-Saharan Africa, emphasis has been more on curative aspect of MCH as a result the indices for maternal and child mortality are relatively poor. This study aims to compare patients’ satisfaction with the quality of maternal and child healthcare services in primary health care facilities in rural and urban communities in Ekiti state. Methods: A cross sectional survey with a multistage sampling technique was used. 366 rural women and 368 urban women utilizing MCH services in randomly selected PHC facilities were recruited by systematic random sampling. Data was collected using questionnaires and analyzed using SPSS version 26.0. Results: This study found that 190 (51.6%) urban respondents received good quality ANC compared to 124 (33.9%) rural respondents. Similarly, 153 (41.6%) urban respondents received good quality delivery care compared to 71 (19.4%) rural respondents. In addition, 306 (83.2%) urban respondents received good quality immunization care compared to 267 (73%) rural respondents. Factors associated with patients’ satisfaction include reception by health staff with 35.8% rural mothers and 53.0% urban mothers satisfied. Also, 38.8% rural women were satisfied with the waiting time as against 26.9% urban mothers. Conclusions: There was a high level of satisfaction amongst both rural and urban women with urban women having a higher percentage.